Post-trade transparency on Nasdaq's national market system1We would like to thank Tom Abbott, Robert Battalio, George Benston, Bill Christie, Larry Fisher, Steve Foerster, Jason Greene, Mike Jensen, Pete Kyle, Paul Laux, Ananth Madhavan, Jean Masson, Junius Peake, Paul Schultz, Paul Seguin, Paul Torregrosa, Dave Whitcomb, as well as seminar participants at the Northern, Southern, and Western Finance Meetings, the Symposium on the Organization of Financial Trade and Exchange Mechanisms, the Symposium in Tribute to Larry Fisher, Baruch College, Georgetown University, the University of Wisconsin-Madison, the SEC, and Paul Seguin (the referee), for helpful comments and suggestions on earlier versions of this paper.1 - Porter, David C; Weaver, Daniel G (Journal of Financial Economics, 1998)
This article examines late trade reporting on the Nasdaq National Market System. A substantial number of trades are reported out-of-sequence on both absolute levels and relative to the combined centralized exchanges. We find minimal support for NASD permitted reasons for the late trade reporting. Evidence suggests that market makers could use late trade reporting to manage the release of information. This evidence is consistent with the hypothesis that the delayed reporting of trades is neither a random occurrence nor fully explainable by factors outside the market maker's control.